2006
DOI: 10.1038/sj.jcbfm.9600439
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Dopamine Transporter Binding Using [18F]FP-β-CIT and Positron Emission Tomography

Abstract: The purpose of this study was to compare different kinetic and semi-quantitative methods for analysing human [18 F]FP-b-CIT studies: plasma input models, simplified (SRTM) and full (FRTM) reference tissue models, standard uptake values (SUV) and SUV ratios (SUVr). Both simulations and clinical evaluations were performed to determine the effects of noise, scan duration and blood volume on Akaike model selection, and on precision and accuracy of estimated parameters. For typical noise levels (COVB2.5%) and scan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
4
32
1
Order By: Relevance
“…For quantitative analysis, static PET images can be used when 18 F-FP-CIT reaches equilibrium binding in the brain, because a simple ratio of regional counts is proportional to binding potential (20,21). However, it remains unclear whether quantitative 18 F-FP-CIT binding potential acquired from PET/MR is concordant with that from PET/CT because of the differences in AC methods and hardware.…”
mentioning
confidence: 99%
“…For quantitative analysis, static PET images can be used when 18 F-FP-CIT reaches equilibrium binding in the brain, because a simple ratio of regional counts is proportional to binding potential (20,21). However, it remains unclear whether quantitative 18 F-FP-CIT binding potential acquired from PET/MR is concordant with that from PET/CT because of the differences in AC methods and hardware.…”
mentioning
confidence: 99%
“…Specific uptake of F-18 FP-CIT of the normal striatum reaches a peak equilibrium state at 90 min or more after injection [5,6]. In Parkinson patients, however, it is thought that the time required to reach this peak equilibrium state is shortened [5], and F-18 FP-CIT activity is likely to washout sooner.…”
Section: Discussionmentioning
confidence: 99%
“…The authours obtained early images 90 min after injection because several studies showed that specific uptake into the corpus striatum peaks after at least 90 min post-administration in healthy controls [5,6]. However, not all patients achieve a peak equilibrium state at 90-120 min, and pseudoeuilibrium is estimated to occur more than 2 h later.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations